Perceptions Of Medical And Dental Students On Online Examinations From Home Setup During 2020-Lockdowns Due To Covid-19 Outbreak In India. - Dr Maitreyee Mutalik,; Dr Madhav Mutalik, (International Journal of Pharma and Bio Sciences, 2022)
The 2020-lockdown shifted the picture of health sciences education to online modality. Since such modality was not commonly used for examinations in health science branches, it was necessary to know what difficulties the students actually face during online examinations. In addition, the present study was undertaken as soon as the trend of online examinations began. Lack of adequate research in this area made it essential to know the responses of students to online assessments, so that necessary modifications could be thought of. The present study was performed to assess the perceptions of medical and dental students towards online examinations. A carefully validated 10-item, anonymous, google-form questionnaire was administered to a large sample size of 369 students in a medical and a dental college. It included items related to laptop availability, device-network issues, question format preferences, typing speed, technical comfort, and honesty level. Results were tabulated, analyzed, and presented as percentages. Sixty percent of students were comfortable with mobile phones rather than laptops and 70 percent of them relied on the mobile data rather than WiFi. Technical comfort level was recorded to be satisfactory, yet due to various factors, 78 percent students preferred actual hard copy examinations. Given a choice between subjective and multiple choice type, 66 percent of students opted the preference for multiple choice questioning. So, although the students were comfortable handling online modality as far as technical issues are concerned, their preference was for offline examinations. It was remarkable that 88 percent students expressed that the honesty level is likely to be less than 75 percent on online examinations, which raised a serious doubt about conducting the examinations by online mode, and that the paper setters need to seriously evolve the examination system for application-based and project-based assessments if the examinations were to be planned online in future.